Corporate Social Responsibility: Completeness and Transparency of Information - M. V. Melnik; M. T. Velikhanov (Учёт. Анализ. Аудит, 2024)
The article presents the results of research in the field of increasing objectivity of information on the social responsibility of the state and business reflected in the reports of economic entities. The main stages of the formation and evolution of this concept in the world scientific literature and in practice of corporate structures are shown. The purpose of the study is to determine the main directions of social responsibility of business and select the forms of their reflection in reporting. Methods for determining social responsibility in individual countries are analyzed. The specifics of its reflection in reporting during the period of centralized economic management and in the post-socialist period of development in Russia has been revealed. Based on the analysis of reports on the social activities of modern corporate structures in Russia, the need to unify and standardize the reporting of corporate structures on social responsibility is justified. The areas of activity in the field of social responsibility, reflected in the form of ESG reporting, are systematized, their specifics and algorithmization of indicators that allow assessing the qualitative and quantitative characteristics of social responsibility are provided. To systematize and classify initiatives in the field of social responsibility, methods of comparative analysis, detailing, classification and determination of the interdependence of social responsibility with the indicators of sustainable development of the organization were used. Proposals have been formulated for structuring reports on the social responsibility of corporate economic entities and management bodies at different levels, taking into account the requirements for their harmonization and compatibility when assessing the effectiveness and efficiency of the state’s social activities. The materials of the article can be used in the development of internal regulations governing social responsibility reporting, as well as in organizing control of information included in the reporting and assessing its reliability.